Pengaruh Dari Love of Money, Sistem Perpajakan, Keadilan Pajak dan Sanksi Pajak Terhadap Persepsi Mahasiswa Mengenai Penggelapan Pajak (Tax Evasion): Studi Kasus pada Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta - Lira Dewi Ariyanti; Lintang Kurniawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of love of money, tax system, tax fairness, and tax sanctions on students’ perceptions of tax evasion. The research employed a quantitative approach using a survey method and explanatory research design. The population consisted of active Accounting students of the Faculty of Economics and Business at Universitas Muhammadiyah Surakarta class of 2022 who had completed Taxation I or Taxation II courses. A total of 110 respondents were selected using proportionate stratified random sampling. Data were collected through a Google Form questionnaire using a 5-point Likert scale. Data analysis was conducted using IBM SPSS Statistics 25 and SmartPLS 4.0 through validity and reliability tests, descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing. The results indicate that love of money and the tax system do not have a significant effect on students’ perceptions of tax evasion. Meanwhile, tax fairness and tax sanctions have a positive and significant effect on students’ perceptions of tax evasion. These findings indicate that perceptions of fairness in the tax system and the strictness of tax sanctions are important factors in shaping students’ views toward tax evasion practices.